2014
DOI: 10.1080/10916466.2013.842586
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Contribution of Gas Hydrate to Corrosion Rate Along the Subsea Pipelines

Abstract: This study developed a corrosion predictive model along the deepwater gas pipelines with hydrate as the corroding agent. The model was developed and simulated with primary focus on the thermodynamic properties of each component of the gas mixture and a solution algorithm written with Matlab 6.5 code. The model was validated by comparing the generated results with the outputs of already established laboratory and mathematical corrosion studies; and the trends of the results obtained comparatively agreed with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the same way, the lumps of hydrate accumulate over time and form larger pipes, which in turn requires more gas transportation along the pipe wall surface [9,23]. This movement induces relative movement between the pipe wall and the hydration plug and activates the development of large-scale erosion corrosion [5,6,14]. Studies [15,17] have shown an increase in the level of localization of corrosion processes, but no explanation for this phenomenon has been provided.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way, the lumps of hydrate accumulate over time and form larger pipes, which in turn requires more gas transportation along the pipe wall surface [9,23]. This movement induces relative movement between the pipe wall and the hydration plug and activates the development of large-scale erosion corrosion [5,6,14]. Studies [15,17] have shown an increase in the level of localization of corrosion processes, but no explanation for this phenomenon has been provided.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, most of the results reported in the literature describe hydrate formation during offshore gas [4,23,25] and gas transportation by offshore or onshore pipelines [9,16,20]. Mathematical models of corrosion effects of gas hydrates [1,2,3,6,21,22,24] do not take into account the effect on the metal or passive films of the hydrate itself, but only the pH of the medium or the concentration of CO2 in the gas. Also, the effect of mechanical stresses and hydrate formation on internal corrosion has not been sufficiently studied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second vital problem hindering the long‐term exploitation of NGH is secondary gas hydrate formation inside the wellbore. Several researchers, such as Koh, 36 Obanijesu et al, 37 Guo et al, 38 Chaudhari et al, 39 and Yu et al, 40 have identified and assessed the blockage risk in the natural gas transportation pipe. Field trial production cases already showed the serious damage caused by secondary gas hydrate formation including blockage of pipes, plugging of valves, and shutting down the production 41–44 .…”
Section: Introductionmentioning
confidence: 99%